Awareness of People on Functions of Local Government in Nepal - Limbu, Lila Prasad (BMC Journal of Scientific Research, 2023)
The article aims to investigate local people's awareness level of the functions of local government in Nepal and identifies the primary factor contributing to raising awareness. The author analyzed 2020 social inclusion survey data using SPSS software, performing a Chi-square test and logistic regression. Results show a high association between gender and awareness level, and development plans are the most significant contributor to increasing awareness levels. Researcher has found that the overall awareness level of people in Nepal is moderate. The author only investigates awareness level and contributing factors of awareness in this article.